Keloid Scarring in the Earlobe: From Piercing to Treatment - Parindita Sarmah; Sagar Gaurkar; Prasad Deshmukh (Journal of Clinical and Diagnostic Research)
A 48-year-old female office worker presented in Ear, Nose and Throat (ENT) Outpatient Department (OPD) with a progressively enlarging, painless mass on both her earlobes, which she noticed about eight months ago. Both the lesions started after she had an ear piercing several years ago; and initially were small but have grown over time. The patient reports occasional itching but no pain, drainage, or signs of infection. She is concerned about the cosmetic appearance of the mass. There is no history of recent trauma to the area, and the patient denies any changes in the surrounding skin. She has no significant medical history and no known allergies. Although her maternal aunt has a history of keloids, there is no family history of similar lesions in other areas of the patient’s body.